(untitled) (COMPETITOR: Jurnal Pendidikan Kepelatihan Olahraga, 2025)
The background of this research is based on the Objective: The objective to be achieved in this research is to analyse the level of basic volleyball smash technique skills in extracurricular participants of SMA Negeri 1 Kertek Wonosobo. Method: This research method is qualitative research, namely, the data collected are in the form of pictures and words, not numbers. Results: Based on the results of data analysis on 20 extracurricular students, it is known that the basic smash technique skills are generally in the "good" category. This is indicated by an average value (mean) of 13.60 out of a maximum score of 20. This value indicates that most students have been able to understand and apply most aspects of the smash technique, although not yet perfectly. Conclusion: Although the mastery of the technique is generally quite good, further, more focused coaching is still needed, especially in the implementation and final stages, to improve technical consistency, movement efficiency, and safety in playing. Suggestion: With directed and systematic coaching, it is hoped that students’ smash technique skills can improve comprehensively and more evenly.